Molecular characterization of foot‐and‐mouth disease viruses circulating in Ethiopia between 2008 and 2019. Issue 6 (1st July 2020) - Gizaw, Daniel; Tesfaye, Yeneneh; Wood, Britta A.; Di Nardo, Antonello; Shegu, Dereje; Muluneh, Ayelech; Bilata, Tsion; Belayneh, Rediet; Fentie, Ayenalem; Asgdome, Hagose; Sombo, Melaku; Rufael, Tesfaye; et al.
Abstract: One of the constraints to controlling foot‐and‐mouth disease (FMD) in East Africa is the incomplete knowledge of the specific FMD virus (FMDV) strains circulating and the way in which these viruses move across countries in the region. This retrospective study focuses on Ethiopia, which has one of the largest FMD‐susceptible livestock populations in Africa. Analyses of FMDV positive samples collected between 2008 and 2019 demonstrate that serotypes O ( n  = 175), A ( n  = 51) and SAT 2 ( n  = 33) were present in the country. Phylogenetic analysis of the VP1 sequences for these viruses showed that there were at least seven different FMD viral clades circulating during this period: O/EA‐3, O/EA‐4, A/AFRICA/G‐I, A/AFRICA/G‐IV, A/AFRICA/G‐VII, SAT2/VII and SAT2/XIII. Although these results only represent a snapshot and might not reflect all FMDV lineages that were present, they highlight the importance of serotype O, as well as the complexity and co‐existence of FMDV serotypes in Ethiopia and surrounding countries. These sequence data also support the idea that there are two FMDV ecosystems existing in East Africa. Data from retrospective studies, such as these presented here, will be beneficial for vaccine selection and vaccination campaigns to control FMDV within Ethiopia.